2004
DOI: 10.1081/rrs-200040324
|View full text |Cite
|
Sign up to set email alerts
|

Role of p38 Mitogen-Activated Protein Kinase in Thrombus Formation

Abstract: The present study was designed to elucidate the role of p38 mitogen-activated protein kinase (p38) in thrombus formation. We used p38alpha heterozygous (p38alpha+/-) mice and used ferric chloride (FeCl3)-induced carotid artery injury as a model of thrombus formation. The time to thrombotic occlusion induced by FeCl3 in p38alpha+/- mice was prolonged compared to that in wild-type (WT) mice. Platelets prepared from p38alpha+/- mice showed impairment of the aggregatory response to a low concentration of U46619, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…Thus, platelets possibly act to facilitate all of the intermediate steps of transvascular metastasis, including tumor cell retention and arrest, subendothelial interaction, and extravasation from the microvasculature. We recently demonstrated that the binding activity of activated platelets from p38␣ ϩ/Ϫ mice to fibrinogen, possibly mediated through integrin ␣IIb␤3, is suppressed compared with the case of platelets from WT mice (9). This clearly indicates that the function of platelets is attenuated in p38␣ ϩ/Ϫ mice compared with WT mice.…”
Section: Reduction Of Tumor Cell-platelet Interaction In P38␣mentioning
confidence: 85%
See 2 more Smart Citations
“…Thus, platelets possibly act to facilitate all of the intermediate steps of transvascular metastasis, including tumor cell retention and arrest, subendothelial interaction, and extravasation from the microvasculature. We recently demonstrated that the binding activity of activated platelets from p38␣ ϩ/Ϫ mice to fibrinogen, possibly mediated through integrin ␣IIb␤3, is suppressed compared with the case of platelets from WT mice (9). This clearly indicates that the function of platelets is attenuated in p38␣ ϩ/Ϫ mice compared with WT mice.…”
Section: Reduction Of Tumor Cell-platelet Interaction In P38␣mentioning
confidence: 85%
“…Tumors were measured along the plane of the body cavity using a hand caliper, and tumor volume was calculated as (length ϫ width) 2 /2. In Vitro Binding of Platelets to Tumor Cells-Platelets were prepared from WT and p38␣ ϩ/Ϫ mice by the method previously described (9). Then platelets were fluorescently labeled with calcein by incubation with 1 M calcein-acetoxymethyl ester (Molecular Probes) for 30 min at 37°C and washed twice with Hepes-Tyrode's buffer (10 mM Hepes, 137 mM NaCl, 2.68 mM KCl, 0.42 mM NaH 2 PO 4 , 1.7 mM MgCl 2 , 11.9 mM NaHCO 3 , 5 mM glucose, pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In platelet biology, MAP kinases have not been studied in detail, although it has been demonstrated that the P2Y 1 ADP receptor activates p38 MAP kinase, and p38-deficient mice have prolonged thrombotic occlusion time in a ferric chloride (FeCl 3 )-induced thrombosis model. 21,22 We, thus, hypothesized that CD36-mediated platelet activation might involve specific members of the src and MAP kinase families.…”
mentioning
confidence: 99%
“…Furthermore, a holistic approach to managing fertility will be necessary, as stem cell transplantation has been reported to affect multiple factors that alter it, including chronic GVHD 7 and longterm psychological health. 8,9 This study demonstrates that the ferocity of acute GVHD affects feracitas and thus raises important…”
mentioning
confidence: 99%